An Analysis of Politeness Strategies Used by Male and Female Teachers in EFL Classes in SMP Negeri 4 Kuta Selatan - ., NI LUH KOMANG DUJANI; ., PROF. DR. NI NYOMAN PADMADEWI, M.A.; ., DR. ASRIL MARDJOHAN, MA. (Jurnal Pendidikan Bahasa Inggris Indonesia, 2017)
Dujani, Ni Luh Komang (2016). An Analysis of Politeness Strategies Used by Male and Female Teachers in EFL Classes in SMP Negeri 4 Kuta Selatan, Thesis, English Education, post Graduated Study Program, Ganesha University of Education. This thesis has been supervised and approved by Supervisor I: Prof. Dr. Ni Nyoman Padmadewi,MA., and Supervisor II: Dr. Asril Marjohan,MA Kata Kunci: Jenis kelamin, Strategi guru, Strategi kesantunan Abstrak Tujuan dari penelitian ini adalah untuk menggambarkan strategi-strategi kesantunan yang digunakan oleh guru laki-laki dan perempuan di kelas EFL di SMP Negeri 4 Kuta Selatan dalam proses belajar mengajar. Peneliti merupakan instrument utama dalam penelitian ini yang mengumpulkan data dengan percakapan video rekaman antara guru dan para siswa. Subjek penelitian ini adalah guru-guru dari SMP Negeri 4 Kuta Selatan yang berbicara kepada siswa mereka. strategi kesantunan yang digunakan oleh guru dianalisis berdasarkan teori kesantunan dari Penelope Brown & Stephen C. Levinson. Hasil penelitian ini menunjukkan bahwa strategi yang digunakan oleh guru laki-laki dan perempuan adalah bald on record, negative politeness, positive politeness, off record dan say nothing. Sebagian besar guru laki-laki digunakan bald on record. Guru perempuan menggunakan strategi imperative secara halus. Ini berarti bahwa guru perempuan lebih menggunakan positive politeness stategy. Guru perempuan menggunakan kata ganti "tolong" untuk membuat ekspresi yang lebih sopan dan menunjukkan kebersamaan antara guru dengan para siswa. Kata Kunci : Jenis kelamin, Strategi guru, Strategi kesantunan ABSTRACT Dujani, Ni Luh Komang (2016). An Analysis of Politeness Strategies Used by Male and Female Teachers in EFL Classes in SMP Negeri 4 Kuta Selatan, Thesis, English Education, post Graduated Study Program, Ganesha University of Education. This thesis has been supervised and approved by Supervisor I: Prof. Dr. Ni Nyoman Padmadewi,MA., and Supervisor II: Dr. Asril Marjohan,MA Key word: Gender, Teachers’ Strategies, Politeness Strategies The objective of the study is to describe the politeness strategies used by male and female teachers in EFL classes in SMP Negeri 4 Kuta Selatan in teaching learning process. The researcher was the key instrument in this study that collected the data by video-recording the utterances between teachers and students. The subject of the study were the teachers of SMP Negeri 4 Kuta Selatan who talked to their students. The politeness strategies used by teachers were analyzed based on Penelope Brown & Stephen C. Levinson theory of politeness. The result of this study showed that the strategies used by male and female teachers were bald on record, negative politeness, positive politeness, off record and say nothing. Mostly the male teacher used bald on record. The female teacher used imperative that softness. It meant that the female teacher used positive politeness. The female teacher used the pronoun “please” in order to make the expression more polite and to show the togetherness between teacher and students. keyword : Gender, Teachers’ Strategies, Politeness Strategies